Development of Rapid Diagnostic Technology for Pig Disease(2) -Rapid detection of PPE in the pig feces - Kim, H.J., RDA, Suwon, Republic of Korea; Hong, J.T., RDA, Suwon, Republic of Korea; Yu, B.K., RDA, Suwon, Republic of Korea; Kim, G.Y., RDA, Suwon, Republic of Korea; Kim, S., Gyeongsang National University, Tongyoung, Republic of Korea (Journal of Biosystems Engineering, 2013)
Purpose: Porcine proliferative enteropathy (PPE), caused by the obligate intracellular bacterium Lawsonia intracellularis, is a widely distributed disease throughout the world causing substantial economic loss. In order to diagnose PPE rapidly, the rapid kit was developed and tested. Methods: In this study, a rapid kit was developed to screen the PPE rapidly at the pig farm. Also, occult blood test with fecal occult blood (FOB) kit was done for detecting the blood in pig feces which might be the evident of hemorrhagic PPE. For developing the kit, we tested fecal samples of PPE infected pigs diagnosed by polymerase chain reaction (PCR) method. Results: With the developed rapid kit, Lawsonia intracellularis was detected in high density emulsion of ileum. On the other hand, the test result of detecting Lawsonia in feces showed too high non-specific response. In addition, nevertheless the FOB test result showed that blood evident could be founded in pig feces, the diagnosing result was not fit to PCR test result, which shows blood in pig feces could be from not only hemorrhagic PPE but also many reasons. Conclusions: To deal with the PPE effectively, it will be better for farmers to screen the PPE in earlier sage with easy and rapid diagnosing tool on farm. This study found out that the rapid kit could detect the Lawsonia intracellularis and hemoglobin in pig feces. However, the non-specific response to negative samples of PPE was too high to use at a pig farm. Further research is needed for lowering the non-specific response with the rapid kit.